Pemanfaatan Sarana Macromedia Flash Dalam Pembelajaran Fiqih Di Kelas V Madrasah Ibtidaiyah Ainul Huda Juwet Ngronggot Nganjuk - Hilyana Diana; A. Jauhar Fuad (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
Multimedia-based learning can certainly present learning material that is more interesting, not monotonous, and facilitates delivery. Students can learn a certain subject matter independently with a computer equipped with multimedia programs. This research method is qualitative. As with the direction of qualitative research, the collected data is analyzed with the provision of intellectual weapons in the form of theory as presented in chapter II to obtain various interpretative descriptions in accordance with the rules of scientific research that are logical and rational. The results of this study are: (1) Utilization of Macromedia Flash as a medium for fiqh learning in Class V Ibtidaiyah Ainul Huda Juwet Nggruk Nganjuk based on the Alessi and Trollip model, which is broadly divided into several stages of use including determining needs and goals, gathering resources, study material, generate ideas, design learning, create material that supports, evaluates and reviews. (2) The effectiveness of using Macromedia Flash in fiqh learning in Class V Madrasah Ibtidaiyah Ainul Huda Juwet Ngronggot Nganjuk is effective enough to support learning in madrasas because it is supported by a very good display quality and easily accepted by students, presenting clear material and displaying concrete things. so students easily understand the material, user interactions and good program interactions so the teacher and students can be active in learning.